Equine innate and adaptive immunity to viral infections - Zhang, Yuwen (Kansas State University, 2008)
Activation of innate immunity through Toll-like receptor (TLR) signaling can also enhance antigen-specific adaptive immunity. TLR9 is an endosomal receptor for unmethylated bacterial and viral cytosine-phosphate-guanine DNA (CpG-DNA). West Nile virus (WNV) infection may result in meningitis and encephalitis in humans and horses, especially aged and immunocompromised individuals. Using flow cytometric analyses and quantitative reverse transcriptase-polymerase chain reaction (RT-PCR), we investigated equine cell-mediated immunity (CMI) to an inactivated West Nile virus vaccine in healthy yearling and adult horses. We also studied the potential of enhancing equine adaptive immunity to viruses and other pathogens by activation of innate immunity though TLR9 signaling pathway. We found vaccination with inactivated WNV vaccine induced strong WNV-specific T helper type 1 (Th1) and Th2 CMI with a Th1 bias, also effectively induced WNV-specific CTLs in yearling horses. In adult horses, the pre-existing Th1 CMI bias against WNV was enhanced following booster vaccination with inactivated WNV vaccine. Molecular characterization and flow cytometric analysis of TLR9 expression using a cross-reactive TLR9 mAb identified high constitutive expression of equine TLR9 in neutrophils (PMNs), CD4[superscript]+ and CD8[superscript]+ T cells and other leukocytes. Conservation of equine TLR9 and a high expression profile among leukocytes suggests that equine TLR9 is a frequent target for unmethylated CpG-DNA, an essential mechanism for the activation of innate immunity. Unmethylated CpG-DNA can significantly activate equine PMNs. It also induces expression of interferon (IFN)-[Alpha], IFN-[Beta], IFN-[Gamma], and interleukin (IL)-12p35 in PBMCs, as well as IFN-[alpha] and IFN-[gamma] in monocyte-derived DCs. Enhanced expression of IFNs in immune cells by CpG-DNA is not only crucial for host viral clearance, but also important in mediating host immune responses due to IFNs' anti-inflammatory effects. Compared to the relatively weaker activation of equine innate immunity by inactivated WNV, the tested CpG-DNA species showed potential as vaccine adjuvants for enhancement of CTLs and Th1 CMI against intracellular pathogens, characterized by significant induction of type I IFNs and Th1-specific cytokines such as IL-12p35 and IFN-γ. These data provide a basis for further investigation of these CpG-DNA species as potentially effective vaccine adjuvants in horses.
Keywords: equine; West Nile virus; adaptive immunity; innate immunity; CpG-DNA; interferon; Health Sciences, Immunology (0982)